SOCIAL RETURN ON INVESTMENT OF THE BIODIVERSITY OFFSET ACTION PLAN OF KHUNG BANGKACHAO, THAILAND - Naklungka, Kanlaya; CAICHOMPOONOPPAKUL, Srinath; TEERSUWAN, Suwanna; BOONNAK, Chairut; NAPATALUNG, Sarawut (Asian Political Science Review, 2023)
The objectives of the research were 1) to study the biodiversity offset activities in the area: Khung Bangkachao 2) to analyze social returns on investment (SROI) of the biodiversity offset action plan. The qualitative, quantitative, and participatory action research methods were employed in this study. By studying document, focus group, study the cost and return data of 31 model farmers. Then, the value was converted into monetary value. The results of this study showed that the biodiversity offset activities, in the case of increasing green area by 10% within the 5-year project duration, the 3 supporting activities with potentials for investment had been selected as follows: 1) financial support for natural resource conservation and restoration, 2) fertilizer support, and 3) solar water system support. It was found that the present value of the investment is 8,500,159 Baht and the present value of return is 12,848,744 Baht. SROI value was 1.51 times. The study showed that the economic returns came from the sales of agriculture products, reducing fertilizer costs, decreasing the electricity costs by solar water system; the social returns caused the employments in the area; and the environmental returns came from the value of perennial plants, ecosystem service value, and reducing the environmental costs of using the solar cells. The private sector can initially support fertilizers or solar water system. Government agencies can use it as an incentive for conservation among stakeholders.